In vivo dosimetry in external beam radiotherapy. Issue 7 (25th June 2013) - Mijnheer, Ben; Beddar, Sam; Izewska, Joanna; Reft, Chester
Abstract : In vivo dosimetry (IVD) is in use in external beam radiotherapy (EBRT) to detect major errors, to assess clinically relevant differences between planned and delivered dose, to record dose received by individual patients, and to fulfill legal requirements. After discussing briefly the main characteristics of the most commonly applied IVD systems, the clinical experience of IVD during EBRT will be summarized. Advancement of the traditional aspects of in vivo dosimetry as well as the development of currently available and newly emerging noninterventional technologies are required for large‐scale implementation of IVD in EBRT. These new technologies include the development of electronic portal imaging devices for 2D and 3D patient dosimetry during advanced treatment techniques, such as IMRT and VMAT, and the use of IVD in proton and ion radiotherapy by measuring the decay of radiation‐induced radionuclides. In the final analysis, we will show in this Vision 20/20 paper that in addition to regulatory compliance and reimbursement issues, the rationale for in vivo measurements is to provide an accurate and independent verification of the overall treatment procedure. It will enable the identification of potential errors in dose calculation, data transfer, dose delivery, patient setup, and changes in patient anatomy. It is the authors' opinion that all treatments with curative intent should be verified through in vivo dose measurements in combination with pretreatment checks.